Peran Entrepreneurial Competence Generasi Penerus Dalam Mengatasi Stagnasi Bisnis dan Meningkatkan Daya Saing Usaha Bakso - Alif Irvansyah; Rina Madyasari; Alfin Nur Arifah; Ardhiansyah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
This study examines the role of entrepreneurial competence among successor generations in overcoming business stagnation and enhancing the competitiveness of a family-owned meatball (bakso) business in Singaparna District, Tasikmalaya Regency. The research employed a qualitative case study approach involving three key informants: the business founder (Mr. Sukiyo) and two successor generations (Mr. Wawan and Mr. Purwanto). Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014) through source and method triangulation.The findings indicate that the entrepreneurial competence of the successor generations is relatively strong in terms of opportunity identification and daily operational management, but remains weak in product innovation, digital marketing, and financial literacy. Business stagnation is influenced by limited innovation, the absence of structured financial records, and the increasing competition within the local culinary business sector. Nevertheless, the business maintains its competitiveness through the authenticity of its recipe and long-term customer loyalty across generations. The stagnation of the business indicates a tendency toward an autonomy crisis, where business management remains largely centralized under the founder, limiting the successors’ opportunities for decision-making and innovation development.